PENGARUH SELF EFFICACY DAN KREATIFITAS TERHADAP MINAT WIRAUSAHA DI INDONESIA - Nur Kholifah, Nuzulia; Saefullah Zevender, Poy; Zaenal Mustofa, Taufiq (Sinau : Jurnal Ilmu Pendidikan dan Humaniora, 2024)
The literature review study was motivated by empirical events that illustrate the increasing number of open unemployment as well as the lack of interest in entrepreneurship among Indonesian people. The literature review study method was carried out by reviewing seven articles obtained from several sources including Google School and e-resources. The article search strategy used available databases. on e-resources, one of which is Google Schoolar with the keywords used in searching for journals, namely: self-efficacy, creativity, interest, entrepreneurship. Researchers use the word "and" as a bloom operator. The use of the bloom operator "And" aims to combine different concepts and aspects as search keywords so that it is more specific for the documents that will be obtained. The results of the literature carried out are the influence of self-efficacy and creativity on entrepreneurial interest in Indonesia. The results of the review article are: 1). increased creativity, 2) increased self-efficacy, 3) personality approach, 4) increased interest in entrepreneurship through entrepreneurship education.